Roles of calcium in geopolymer containing paper mill sludge ash - Norbaizurah, Rahman; Andri, Kusbiantoro; Nabilah, Mamat; Khairunisa, Muthusamy; Mohd Mustafa Al Bakri, Abdullah (Trans Tech Publications, 2018)
High amount of calcium oxide (CaO) in source material is known to positively influence the mechanical strength of fly ash based geopolymer. This study was conducted to investigate the suitability of paper mill sludge ash (PMSA) to partially replace fly ash in geopolymer mortar based on the characteristic of its degree of reaction. Fly ash was activated by a combination of sodium silicate and 6M sodium hydroxide solution. The mixtures were designed to replace fly ash content with PMSA at 5%, 10%, and 15% (by weight of fly ash). To observe its effect on the degree of reaction, the specimens were cured in three different temperatures, which are 30°C, 60°C, and 90°C for 24 hours. After 24 hours, the hardened specimens were demoulded and stored in room temperature until the testing days. Measurement on fresh geopolymer properties was conducted with setting time and flowability tests, while degree of reaction test was conducted on the hardened specimen at 1 and 28 days. Based on the result, 5% of PMSA demonstrated superior degree of reaction than other mixtures in every curing temperature. It signifies the prospective benefit of PMSA for further use as an additive in geopolymer.